Driving factors of tree biomass and soil carbon pool in xerophytic forests of northeastern Argentina - Sione, Silvana María José; Wilson, Marcelo German; Ledesma, Silvia Gabriela; Gabioud, Emmanuel Adrian; Oszust, José Daniel; Rosenberger, Leandro Javier (Springer, 2024)
Background: The conversion of forests into agricultural lands can be a threat because the forests carbon stored could be a source of emissions. The capacity to improve the predictions on the consequences of land use change depends on the identification of factors that influence carbon pools. We investigated the key driving factors of tree biomass and soil carbon pools in xerophytic forests in northeastern Argentina. Based on analyses of forest structure variables and abiotic factors (topography and soil properties) from 18 mature forests, we evaluated carbon pools using uni- and multivariate (redundancy analysis) methods. Results: The total carbon pool was estimated at 102.4 ± 24.0 Mg ha−1. Soil organic carbon storage is the single largest carbon pool relative to tree biomass, representing 73.1% of total carbon. Tree canopy cover and basal area were positively correlated with biomass carbon pool (r = 0.77 and r = 0.73, p < 0.001, respectively), proving to be significant drivers of carbon storage in this compartment. Slope, soil clay content and cation-exchange capacity had a better explanation for the variability in soil carbon pools, and all showed significant positive correlations with soil carbon pools (r = 0.64, 0.60 and 0.50; p < 0.05, respectively). The vertisols showed a 27.8% higher soil carbon stock than alfisols. Conclusions: The relevance of our study stems from a dearth of information on carbon pools and their drivers in xerophytic forests, and in particular, the importance of this ecosystems’ type for Argentina, because they cover 81.9% of native forest area. Basal area and tree canopy cover exert a strong effect on the carbon pool in tree biomass but not in the soil. The results suggests that there is a potentially major SOC accumulation in forests located in slightly sloping areas and soils with higher topsoil clay content, such as vertisols. This could provide an important reference for implementing forestry carbon sink projects.